Comparing Monetary Policy Transparency. The Eijffinger and Geraats Index - a Comment - Carl Andreas Claussen (Norges Bank, 2008)
There is by now a large volume of literature on central bank transparency and communication. One branch of this literature compares transparency across central banks and over time. Recent contributions in this vein are Eijffinger and Geraats (2006), Dincer and Eichengreen (2007), and Geraats (2008), who all use an index developed by Eijffinger and Geraats (2006). In this note I argue that the index can be very misleading. The argument is illustrated by the case of Norway, which has received a relatively low score on the index.
hdl:11250/2507958
Keywords: 330